A model of the three-dimensional structure of human interferon responsive factor 1 and its modifications upon phosphorylation or phosphorylation-mimicking mutations. Issue 17 (22nd November 2019) - Storchi, Loriano; Remoli, Anna Lisa; Marsili, Giulia; Acchioni, Chiara; Acchioni, Marta; Battistini, Angela; Sgarbanti, Marco; Marrone, Alessandro
Abstract: Interferon responsive factor 1 (IRF-1) is a pleiotropic transcription factor, possessing non-redundant biological activities that depend on its interaction with different protein partners and multiple post-translational modifications including phosphorylation. In particular, a 5′-SXXXSXS-3′ motif of the protein represents the target of the Iκ B-related kinases, TANK-binding kinase (TBK)-1 and inhibitor of nuclear factor kappa-B kinase (IKK)-ε. Here, a 3D model of human IRF-1 was determined by using multi-template comparative modeling and molecular dynamics approaches. Models obtained through either phosphorylation or aspartate mutation of residues 215, 219 and 221 were also calculated and compared to the wild type. Calculations indicated that each of these modifications mainly induces a rigidification of the protein structure and only slightly changes in electrostatics and hydrophobicity of IRF-1 surface, resulting in the impairment of the capacity of IRF-1 containing as partate mutations (S221D and S215D/S219D/S221D) to synergize with tumour necrosis factor (TNF)-α stimulation in inducing interferon (IFN) promoter-mediated reporter gene activation. Therefore, these changes are qualitatively correlated to the amount of negative charge located on the 215–221 segments of IRF-1 by phosphorylation or aspartate mutation. Hypotheses on the structural mechanism that governs the phosphorylation-related damping of IRF-1 activity were also drawn. Communicated by Ramaswamy H. Sarma